Effect of different sprint training regimes on the oxygen delivery-extraction in elite sprinters - Ben-Sira, D.; Amir, R.; Amir, O.; Yamin, C.; Eynon, N.; Meckel, Y.; Sagiv, M.; Sagiv, M. (The Journal of Sports Medicine and Physical Fitness, 2010)
AIM: The effects of sprint training regimes of varying distance schedules on the oxygen delivery-extraction relationship were investigated in 15 young (22±1 years) healthy males national-level sprinters. METHODS: During one session subjects performed four sprints, in a schedule of increasing distance order (100, 200, 300 and 400 m), and during the other session, in a schedule of decreasing distance order (400, 300, 200, and 100 m). All sprint bouts were performed on a treadmill at a speed of 22 km/h, which corresponds to 85% of subjects` maximal speeds. The order of the running sequences during sessions was balanced over subjects. RESULTS: During both sprint schedules, all variables except for oxygen extraction in the incremented training regime, increased significantly from rest to exercise. Training regimes were not different with regard to cardiac output and absolute oxygen uptake. However, the decreasing compared to the increasing scheme was characterized by significantly (P<0.05) higher mean values of heart rate (194.5±4.1 185.2±5.7 beats/min, respectively), oxygen extraction (54.3±3.8 and 47.1±3.4 mL/L, respectively) and lactate (10.6±0.5 and 9.2±0.7 mmol/L, respectively), while stroke volume was significantly (P<0.05) lower (100.4±4.5 and 109.7±4.4 mL, respectively). CONCLUSION: The present study indicates that in sprinters performing a similar distance at the same speed, but under different training regimes interplay exists between oxygen delivery and extraction, suggesting a link between the type of training scheme and physiological cardiovascular and skeletal muscle metabolic adaptations. This may explain the absence of differences between the conditions in absolute oxygen uptake and peak power output.